Exposure to Intimate Partner Violence and Hypertension Outcomes among Young Women in South Africa - Nicole De Wet-Billings; Motlatso Godongwana (International Journal of Hypertension)
Hypertension and intimate partner violence is affecting longevity and quality of life among women worldwide. In this study, intimate partner violence is identified as a risk factor for hypertension outcomes among young women in South Africa. Using a nationally representative sample of 216 (N) young women (15–34 years old) from the South African Demographic and Health Survey, this study uses cross-tabulations and logistic regression methods to identify the odds of hypertension outcomes. Results show that between 20 and 41% of 15–34-year-old women have hypertension. Further, 68% of women with hypertension experienced physical intimate partner violence. Finally, the odds of hypertension are increased if young women experience physical (OR: 4.07; CI: 1.04726–15.82438) or sexual (OR: 2.56; CI: 1.18198–5.55834) intimate partner violence. Efforts to reduce hypertension outcomes in the country should include intimate partner violence awareness and assistance.